Identifying and reducing risks in functional endoscopic sinus surgery through a hierarchical task analysis. Issue 1 (28th November 2018) - Corbett, Mel; O'Connor, Paul; Byrne, Dara; Thornton, Mona; Keogh, Ivan
Abstract : Objective: To develop a hierarchical task listing of steps required to perform successful Functional Endoscopic Sinus Surgery (FESS). To complete a technical and human factor analysis of tasks resulting in the identification of errors, frequency of occurrence, severity, and reduction through remediation. Methods: A triangulation of methods was used in order to derive the steps required to complete a FESS: 1) a literature review was carried out of published descriptions of FESS techniques; 2) observations of three FESS; 3) interviews with surgeons on FESS techniques. Data sets were combined to develop a task analysis of a correct approach to conducting FESS. A review by 12 surgeons, and observation of 25 FESS resulted in refinement of the task analysis. With input from five consultant surgeons and one consultant anesthetist, a Systematic Human Error Reduction and Prediction Approach (SHERPA) was used to identify the risks and mitigating steps in FESS. Results: Ten tasks and 49 subtasks required for a correct approach to completing FESS were identified based on literature review and expert consensus. A risk score for each subtask was calculated from a suitable risk matrix. Risk reduction methods at each subtask were detailed. High‐scoring subtasks were evaluated and varying strategies examined to reduce the likelihood and mitigate the impact of error. The study demonstrates the usefulness of the HTA and SHERPA approach in standardization and optimization of clinical practice in order to improve patient safety. Conclusion: Hierarchical Task Analysis and SHERPA are valuable tools to deconstruct expert performance and to highlight potential errors in FESS. The HTA and SHERPA approach to surgical procedures are useful learning and assessment tools for novice surgeons. The information derived offers the opportunity to improve surgical training and enhance patient safety by identifying high‐risk steps in the procedure, and how risk can be mitigated. Level of Evidence: 2c Outcomes Research